Thinking of the smart network development caused by collective motion:situational-section fitting network - Jiangxing WU; Yuxiang HU; Yufeng LI (Dianxin kexue)
Exploring the way of global coordinated controlling of internet resources for the consistency of user experience,is a difficult problem to be solved urgently in the development of smart network at present.Inspiration was got from the natural collective motion,and a coordinated fitting scheme of globe-domain resources based on node self perception,autonomous decision and automatic adjustment——situational-section fitting network (SiFiNet) was proposed.The basic concept of situational network was given,and the core mechanisms of scene perception modeling,scene fitting decision and service adaptive loading were discussed,which provided a possible solution for the development of smart network.